2005
DOI: 10.1007/11555261_14
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Display Configurations on Document Triage

Abstract: Document triage is the practice of quickly determining the merit and disposition of relevant documents. This practice involves selection of documents from a document overview and quick forms of reading: skimming, reading short portions of a longer document, and navigating through headings, indices, and tables of contents. Earlier studies of document triage practice showed considerable overhead related to window management during transitions between the document overview and reading interfaces. This study exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 9 publications
2
25
1
Order By: Relevance
“…Recent papers by Badi [1] and Bae [2], Wacholder [15] and others have pointed the way to a more detailed consideration of the interaction that occurs during document triage, in electronic and physical information media.…”
Section: Related Workmentioning
confidence: 99%
“…Recent papers by Badi [1] and Bae [2], Wacholder [15] and others have pointed the way to a more detailed consideration of the interaction that occurs during document triage, in electronic and physical information media.…”
Section: Related Workmentioning
confidence: 99%
“…The current research into triage is fragmented, and this no doubt explains the lack of such a model. Available reports focus on very specific aspects or external aspects rather than document triage generally [1,2,3,5,18].…”
Section: Introductionmentioning
confidence: 99%
“…This modeling can also be based on user behavior during document triage and on the types of external information structures that people build for information that is important to a task (e.g. categories and spatial structures) [2][19] [22].…”
Section: Document Triagementioning
confidence: 99%
“…For example the two media have different affordances: participants reported that annotation was easier on paper, for instance. Moreover, the affordances of tools used during triage (such as spatial hypertext [19] and display configuration [2]) can have an impact on the practice of triage.…”
Section: Document Triagementioning
confidence: 99%
See 1 more Smart Citation